Plan de negocios para la creación de un centro de confecciones deportivas y casuales, en la ciudad de Ventanas, a partir del año 2012 - Pacherre Zapata, Cecilia Annabel (2012)
The academic foundation of the profession of Management generates entrepreneurship initiatives, which together with the decision of the researcher, led establish knowledge about the production and marketing of sportswear and casual. It is our professional baseline and experience directed at the area of clothing, activity that the researcher has developed for many years. Your application will be evidenced by structuring; organizing and strengthening a small apparel company, and develop a business proposition of these products in the city of Windows, from the year 2012. It consolidates project information with methodological structuring and gathering knowledge and techniques serving to demonstrate the feasibility of the business plan, focused as an application for economic development and production of a small business. Building a business plan aimed at creating a center of apparel and casual sportswear, will satisfy a wide range of market and promote a small business to profitability in the town of Windows, from the year 2012. Thus fulfilling the objectives of the project and with the hypothesis suggested.